Digital Photographies of Silek Rantak Kudo Dance : The West Sumatra Folklore Preservation - Rustiyanti, Sri; Listiani, Wanda; Ningdyah, Anrilia E.M.; Dwiatmini, Sriati; Suryanti (Institut Seni Indonesia Denpasar, 2025)
The Silek Rantak Kudo Dance, a rich expression of Indonesian folklore and cultural identity—particularly in West Sumatra—requires preservation. To support this effort, a photographic experiment was conducted to explore visual representations capable of conveying the folkloric elements embedded in the dance. Notably, there is a lack of scholarly literature on dance photography in Indonesia, making this study a pioneering contribution to the field. The experiment produced 66 photographs of the Silek Rantak Kudo Dance, with 10% selected for inclusion in a questionnaire aimed at evaluating whether respondents could effectively perceive the folkloric content. This research employed Visual Arts-Based Research Practices, with data collected through a literature review and questionnaires completed by 396 participants. Findings indicate that dance photography of Silek Rantak Kudo should emphasize traditional elements in both movement and visual representation to ensure its recognition as a traditional West Sumatran art form. Furthermore, the study demonstrates that photographic techniques—such as motion photography and posed imagery—can serve as effective tools for promoting and preserving the dance on social media among the Indonesian public.